Análise aerodinâmica de um protótipo de eficiência energética por simulação Fluidodinâmica Computacional (CFD) - Bosch, Bruno (2016)
Studies on vehicular aerodynamics have shown great intensity in the last decades, this being caused by the great interest of the population by means of more efficient automotive, which in turn pollute less the environment. And to uncover how aerodynamics is closely linked with fuel consumption, as trawling emerges as an opposing force of movement, automotive industries have stepped up their search for tools that can predict automotive performance. In this work, a computational model was developed to analyze the flow generated on the energy efficiency prototype of the Pato a Jato team of UTFPR, Pato Branco campus. Through the use of Ansys Workbench® software. The use of computational tools allows achieving the results with a lower cost and time involved. The objective of this work is to obtain a reduction in drag by proposing modifications in the geometry of such prototypes. For this, first three different meshes were tested to verify which one was best suited to solve the problem. After determining the best mesh, two variables that influence vehicle aerodynamics were studied, being they the angle of rear convergence and the frontal slope. The results found corresponded to those expected. And this study demonstrated that trawling undergoes more changes to changes in the rear geometry rather than changes in the frontal region.